The Hidden Cost of Code Completion: Understanding the Impact of the Recommendation-list Length on its Efficiency. - Jin, Xianhao; Servant-Cortés, Francisco Javier (ACM, 2018)
Automatic code completion is a useful and popular technique that software developers use to write code more effectively and efficiently. However, while the benefits of code completion are clear, its cost is yet not well understood. We hypothesize the existence of a hidden cost of code completion, which mostly impacts developers when code completion techniques produce long recommendations. We study this hidden cost of code completion by evaluating how the length of the recommendation list affects other factors that may cause inefficiencies in the process. We study how common long recommendations are, whether they often provide low-ranked correct items, whether they incur longer time to be assessed, and whether they were more prevalent when developers did not select any item in the list. In our study, we observe evidence for all these factors, confirming the existence of a hidden cost of code completion.
Keywords: Software - Mantenimiento; Software engineering; Software maintenance; Software tools; Programming environments